Predictors of Atrial Fibrillation Risk in Hypertrophic Cardiomyopathy - Tuluce, Kamil (J Atr Fibrillation, 2015)
Hypertrophic cardiomyopathy (HCM) is a genetic cardiovascular disease that predisposes individuals to the development of arrhythmias. The most common sustained arrhythmia is atrial fibrillation (AF). Compared with the general population, patients with HCM are more prone to the development of AF. To avoid embolic complications and the clinical deterioration caused by the development of AF in HCM, identifying patients with a tendency toward AF might affect the management of HCM. In this review, we evaluated the predictors of AF development in patients with HCM.